Medicinal plants and natural products for treating overactive bladder - Huanxian Chen; Maggie Pui Man Hoi; Simon Ming Yuen Lee (BMC, 2024)
Abstract Background Overactive bladder (OAB) presents a high prevalence of 16-18% worldwide. The pathophysiology of OAB is still poorly understood while effective therapy or countermeasure are very limited. On the other hand, medicinal plants and herbal remedies have been utilized for treating lower urinary tract symptoms (LUTS) in both Eastern and Western cultures since ancient times. In recent years, accumulating progress has also been made in OAB treatment research by using medicinal plants. Methods Relevant literature on the studies of medicinal plants and herbs used to treat OAB was reviewed. The medicinal plants were summarized and categorized into two groups, single-herb medications and herbal formulations. Results The present review has summarized current understanding of OAB's pathophysiology, its available treatments and new drug targets. Medicinal plants and natural products which have been used or have shown potential for OAB treatment were updated and comprehensively categorized. Studies on a wide variety of medicinal plants showed promising results, although only a few phytochemicals have been isolated and identified. Until now, none of these herbal compounds have been further developed into clinical therapeutics for OAB. Conclusions This review provides the basis for discovering and designing new phytopharmaceutical candidates with effective and well-tolerated properties to treat OAB. Increasing evidences indicate new strategies with alternative herbal treatment for OAB have high efficacy and safety, showing great promise for their clinical use. Future studies in a rigorously designed controlled manner will be beneficial to further support the eligibility of herbal treatment as OAB therapeutics.